Patient-Reported Olfactory and Sinonasal Outcomes following Endoscopic Transsphenoidal Pituitary Surgery: A Prospective Evaluation - Sunderland, Geraint J.; Ellenbogen, Jonathan R.; Gilkes, Catherine E.; Sinha, Ajay K. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Endoscopic endonasal transsphenoidal surgery (EETS) results in disturbance of nasal mucosa and airflow. Previous studies have demonstrated associated sinonasal morbidity but have not prospectively assessed olfactory function.To obtain prospective objective measure of sinonasal morbidity associated with EETS.We report our prospective patient-reported outcome study of 20 unselected, consecutive patients undergoing EETS. Baseline assessment of olfactory function was performed using the validated University of Pennsylvania Smell Identification Test alongside quality of life (QoL) assessments using the 22-item Sino-Nasal Outcomes Test (SNOT-22) and Anterior Skull Base Questionnaire (ASBQ) prior to surgery. Repeat olfactory function testing and QoL questionnaires were performed at 3 months and 12 months postoperatively. All patients underwent pituitary surgery and there was one extended anterior approach.Mean olfactory function score was worse at 3 months (25.9) compared with baseline (30.5), p = 0.02. This improved back toward baseline at 1 year (29.4). Three patients (15.8%) had significant residual olfactory impairment at 1 year. There were no significant differences in SNOT-22 score or ASBQ at 3-month or 1-year follow-up. EETS is associated with minor disturbances in olfactory and sinonasal QoL.Formal assessment of olfactory function has proven more sensitive in identifying deficiencies in olfaction following surgery; however, there is little or no correlation with QoL scores.
Keywords: pituitary surgery; transsphenoidal surgery; smell test; quality of life; patient-reported outcome measures